Treatment of Water Contaminated with Diesel Using Carbon Nanotubes - Pierantonio De Luca; Carlo Siciliano; Janos B.Nagy; Anastasia Macario (Applied Sciences, 2023)
The purpose of this research was to evaluate the adsorbent properties of carbon nanotubes by investigating, in particular, the possibility of their use in the purification of water contaminated with automotive diesel, caused, in most cases, as a result of spillage from underground tanks, leaks from pipelines, traffic accidents, etc. In particular, we investigated whether the high molecular weights of the hydrocarbon molecules present in diesel could influence the adsorption capacity of carbon nanotubes. Initial systems consisting of water and diesel were treated with different amounts of carbon nanotubes. The final post-adsorption phases were characterized using NMR analysis, FT-IR spectroscopy and TG-DTG-DTA thermal analysis. Carbon nanotubes showed great efficiency in the adsorption of diesel, the possibility of their reuse in several adsorption cycles and the consequent recovery of the adsorbed diesel and of the treated water.